The new cross-sectorial agency in Norway for archives, libraries and museums: plans and perspectives - Østby, Jon Birger (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
First, I would like to thank for being invited to present the new cross-sectorial agency in Norway for archives, libraries and museums at the LIBER conference! I will start my presentation by giving you a brief introduction to the Norwegian Archive, Library and Museum Authority with regard to background for the emergence, organization and objectives. Furthermore, I will present some of our main priorities. Although this is a conference, which focuses on library issues, I find it important to mention initiatives for the two other sectors as well, in order to give you a broader picture of the new institution.